Assessment Report on Banso District, Bamenda Division, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1923)
This file contains colonial memoranda and assessment report on Banso District, Bamenda Division, Cameroons Province
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Banso; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies